Experimental understanding of the relationship between combustion/flow/flame velocity and knock in a hydrogen-fueled Wankel rotary engine. (1st November 2022) - Meng, Hao; Ji, Changwei; Yang, Jinxin; Chang, Ke; Xin, Gu; Wang, Shuofeng
Abstract: Driven by issues such as global warming, there is currently great interest and significance in developing zero carbon-emission internal combustion engines. Limited by structural and sealing requirements, there are no experimental studies related to combustion velocity measurement of the hydrogen-fueled Wankel rotary engine (HWRE) with excellent power performance, which is important to investigate its knock characteristic. In this work, a combustion velocity measuring method of dual spark plug HWRE is proposed, besides the obtained combustion, flow and flame velocities are correlated with the knock to explore their influence on the HWRE knock characteristics. The study found that adopting dual spark plugs in HWRE is necessary to reduce the negative impact of the flame not being able to propagate against the flow field. Besides, excess air ratio affects the combustion velocity of HWRE by changing the flame velocity, while the engine speed affects the combustion velocity of HWRE by changing the flow velocity, which basically does not affect the flame velocity. The knock level of HWRE is influenced by its flame velocity and flow velocity, both of which are positively correlated to the knock intensity and the latter has a more significant effect. Highlights: A method of measuring Wankel rotary engine combustion velocity is proposed. Quantifying the combustion, flow and flame velocity of hydrogen Wankel rotary engine. Investigating the influence of excess air ratio and engine speed. Quantifying the relationship between knock intensity and above three velocities.